Гібридний контактор з додатковими рухомими контактами - Сосков, А.Г.; Дорохов, О.В.; Сабалаєва, Н.О.; Соскова, І.О.; Форкун, Я.Б. (Електротехніка і електромеханіка, 2011)
A hybrid contactor with a subsidiary movable contact to provide zero galvanic coupling between the current network and load in the contactor off mode is proposed, which allows essentially expanding hybrid contactor application field.